The contribution of the European Union to global climate change governance: explaining the conditions for EU actorness - Carolina B. Pavese (Revista Brasileira de Política Internacional, 2012)
As a regional organization, the European Union's role in global climate governance faces constraints that do not apply to other members of the United Nations Framework Convention on Climate Change (UNFCCC) and Kyoto Protocol. Addressing that uniqueness, this article provides a theoretical and empirical analysis of how the elements of actorness (recognition, capability, opportunity and cohesion) shape the EU's engagement with the international climate change regime.